PERSONALIZED LEARNING IN THE AVIATION INDUSTRY: DEVELOPMENT OF AIRPORT AND HELIPORT TEACHING MATERIALS BASED ON BLENDED LEARNING - Irfan, Irfan; Suhanto, Suhanto; Jaya, Irwan; Sukarwoto, Sukarwoto (JURNAL EDUSCIENCE, 2025)
Purpose – Blended Learning in the Aerodrome & Heliport course combines theory and practice flexibly and interactively. Conventional methods are less effective due to the lack of active involvement and limited access to learning materials. This study aims to develop blended learning-based learning materials to improve student competency in the Aerodrome & Heliport course at the Makassar Aviation Polytechnic. In addition, this study was conducted due to the low academic achievement of students, with 20% failing the course.Methodology – The research used the Research and Development (R&D) model. However, only the first three stages are worked on: define, design, and develop. This research involves 24 air transport management diploma program students as respondents and two radio aids to air navigation instructor respondents. Data were collected through survey, interview, observation, and documentation. Assessments from experts on blended Learning and aviation education using qualitative and quantitative analysis methods were conducted to assess the validity of the developed teaching materials.Findings – The study demonstrated that blended Learning considerably raised student proficiency. The methodically created instructional materials received a high validity grade from specialists who rated them as "Very Valid" (Va ≥ 0.80). Additionally, the study discovered that using interactive teaching resources—like video tutorials, simulations, and structured learning modules—helped students comprehend complex ideas.Contribution – On a practical level, this study provides real solutions to address learning challenges in aviation vocational education by combining online and in-person Learning. The teaching materials developed can be used as a model by other similar institutions to design tech-based curricula that meet industry needs. Theoretically, the study deepens our understanding of how effective blended Learning can be in technical education, especially in aviation, by emphasizing the need for flexible instructional design that supports higher-order thinking Skills (HOTS).